The development of the Marital Satisfaction Scale (MSS) [Evlilik Doyum Ölçegi'nin (EDÖ) Gelistirilmesi] - (:unkn) unknown (My University, 2013)
In this study, the process of developing the Marital Satisfaction Scale (MSS) aiming to support studies in the field of marital satisfaction and to obtain information about couples in a short time through psychological counseling is discussed. The scale including 101 yes-no items aiming to reveal couples' opinions about their marriages was designed in parallel with similar scales developed abroad for similar purposes. The scale is comprised of two parts. The first part contains 92 items related to the sub-dimensions of the marital satisfaction. On the other hand, the second part of the scale dealing with the effect of "understanding of parenting" on the marital satisfaction includes 9 items to be responded by individuals with children. In the process of developing the scale, 341 people were given the whole scale and 270 people who have children were given the second part of the scale to carry out the statistical calculations. As a result of the item total, item remaining and discriminant analysis of the scale, the results were found to be significant at the level of p<.001. Through Cronbach α, Spearman Brown and Guttman Split-Half techniques, reliability values between r=.93 and .97 were found. The reliability values of the part of the scale administered to people with children about "understanding of parenting" was found to be between r=.81 and .86. The factor analysis revealed that the first sub-dimension of the scale assesses the "marital harmony" which is comprised of the "relationship happiness", "conflict" and "closeness" sub-scales. Other sub-dimensions are "anger", "communication with the spouse's family ", "economic understanding", and "understanding of parenting". © 2013 Educational Consultancy and Research Center.
Keywords: Marital Relationship; Marital Satisfaction; Marital Satisfaction Scale; Married Couples